2020
DOI: 10.1016/j.cdtm.2020.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow mesenchymal stem cell transplantation downregulates plasma level and the microglia expression of transforming growth factor β1 in the acute phase of cerebral cortex ischemia

Abstract: Background Both bone marrow mesenchymal stem cell (BM-MSC) and transforming growth factor-β1 (TGF-β1) have a strong anti-inflammatory capacity in stroke. But their relationship has not been well addressed. In this study, we investigated how intravenous BM-MSC transplantation in rats effected the expression of TGF-β1 48 h post cerebral ischemia, and we analyzed the main cells that produce TGF-β1. Methods We used a distal middle cerebral artery occlusion (dMCAO) model in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…117 full-text articles were assessed for inclusion, with 28 excluded (Figure 1). Three of these were excluded due to use of an inappropriate model [30][31][32] , two for being performed in vitro 33,34 , two due to not being relevant to TGF-β1 35,36 , eight for not having a full text available [37][38][39][40][41][42][43][44] , one due to a lack of experimental controls 45 and 12 for measuring inappropriate outcomes or measuring TGF-β1 as part of a large panel of molecules [46][47][48][49][50][51][52][53][54][55][56][57] A further four studies used photothrombosis to induce focal cortical ischemia following administration of a photosensitizing agent, whilst two studies utilized the injection of autologous blood clots to the internal carotid artery.…”
Section: Search Resultsmentioning
confidence: 99%
“…117 full-text articles were assessed for inclusion, with 28 excluded (Figure 1). Three of these were excluded due to use of an inappropriate model [30][31][32] , two for being performed in vitro 33,34 , two due to not being relevant to TGF-β1 35,36 , eight for not having a full text available [37][38][39][40][41][42][43][44] , one due to a lack of experimental controls 45 and 12 for measuring inappropriate outcomes or measuring TGF-β1 as part of a large panel of molecules [46][47][48][49][50][51][52][53][54][55][56][57] A further four studies used photothrombosis to induce focal cortical ischemia following administration of a photosensitizing agent, whilst two studies utilized the injection of autologous blood clots to the internal carotid artery.…”
Section: Search Resultsmentioning
confidence: 99%
“…These results indicated that MSC could also be developed as a prophylactic therapy for patients post-stroke besides therapeutic treatment. Most preclinical studies showed that the number of activated microglia was significantly decreased by MSC or EV administration ( 15 , 61 , 63 – 65 , 75 , 77 82 , 84 , 85 , 88 ). Notably, three-dimensional (3D) spheroid cultured MSCs have been demonstrated to exhibit decreased cell size; therefore, these cells are not likely to be entrapped in lung tissue after IV infusion ( 39 ).…”
Section: Morphology Of Microglia In the Healthy And Stroke Brainmentioning
confidence: 99%
“…Compared with 7 days post-ischemia, administration of either allogeneic (rMSCs) or xenogeneic (hMSCs) stem cells at 1 day resulted in a significantly greater recovery of motor behavior after MCAO that was possibly related to an increase in activated microglia (CD11) in the infarct region ( 76 ). Transplantation of BMSC reduces the proportion of Iba-1 + microglia cells expressing TGF-β in the cerebral infarction area 48 h after ischemia ( 88 ). IV allogenic BMSC significantly increased the inflammation, evidenced by an increase of TNFαand IL-1βand the number of Iba+ microglia/macrophages in the ischemic core cortex at day 2 after MCAO ( 83 ).…”
Section: Morphology Of Microglia In the Healthy And Stroke Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…For decades, mesenchymal stem cells (MSCs) have been demonstrated their multiple differentiation capacities into bone tissue, cartilage tissue, and their clinical treatment potential on a variety of disease such as cerebral infarction. 1 , 2 , 3 In the case of osteogenic differentiation of MSCs, there are numerous methods and specific ways that can successfully induce MSCs differentiating into osteoblastic linage, including osteoinduction media, pharmaceuticals, growth factors, genes, biomaterials, even mechanical stress stimulations, when used singly or combined together. 4 , 5 , 6 , 7 Yet, there is still a lack of knowledge for understanding the mechanism of how MSCs differentiate into osteogenic linage cells under these massive conditions.…”
Section: Introductionmentioning
confidence: 99%